2003
DOI: 10.2527/2003.811261x
|View full text |Cite
|
Sign up to set email alerts
|

Age at puberty, total fat and conjugated linoleic acid content of carcass, and circulating metabolic hormones in beef heifers fed a diet high in linoleic acid beginning at four months of age1

Abstract: In the current study, we hypothesized that diets high in linoleic acid would increase conjugated linoleic acid (CLA) tissue content, reduce adiposity and leptin production, and result in an increase in the age at puberty in heifers. Heifers were weaned and blocked by body weight (heavy, n = 10, and light, n = 10) and allocated randomly within block to receive isocaloric and isonitrogenous diets with either added fat (HF, n = 10) or no added fat (C, n = 10) from 4 mo of age until post-pubertal slaughter. Whole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
4
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 30 publications
5
33
4
4
Order By: Relevance
“…The circulating concentration of IGF-1 is highly correlated to BW and growth rate during the period of pre-pubertal growth (Lammers et al, 1999;Brickell et al, 2009a). In contrast, Garcia et al (2003) found that IGF-1 levels in beef heifers declined in the 10 weeks preceding puberty. These differences may relate to differences in ages at which puberty is reached and/or nutritional management in different studies.…”
Section: Timing Of Pubertymentioning
confidence: 55%
“…The circulating concentration of IGF-1 is highly correlated to BW and growth rate during the period of pre-pubertal growth (Lammers et al, 1999;Brickell et al, 2009a). In contrast, Garcia et al (2003) found that IGF-1 levels in beef heifers declined in the 10 weeks preceding puberty. These differences may relate to differences in ages at which puberty is reached and/or nutritional management in different studies.…”
Section: Timing Of Pubertymentioning
confidence: 55%
“…Among the heifers fed SB and responding to estrous synchronization in the preliminary experiment, the interval from PGF 2α to estrus (76.6 h) was prolonged compared with heifers fed diets containing WCGF (69.2 h). Studies are limited on the use of fat supplements in replacement heifer diets; however, these studies agree with others demonstrating no beneficial or detrimental effect of supplementing fat from a variety of sources at inclusion rates of 2 to 5% of DM (Funston et al, 2002;Garcia et al, 2003;Howlett et al, 2003).…”
Section: Expmentioning
confidence: 54%
“…Supplementing Holstein heifers with rumen bypass fatty acids or CLA from 3 to 5 mo of age until the third postpubertal estrus had no effect on plasma leptin (Block et al, 2003). Similarly, feeding sunflower oil to heifers beginning at 4 mo of age did not change leptin concentration (Garcia et al, 2003). Leptin also was unchanged by addition of 6% sunflower oil to the finishing diet of Wagyu or Limousin steers (Johnson et al, 2001b).…”
Section: Discussionmentioning
confidence: 88%